Pengaruh Insentif Eksekutif, Corporate Risk dan Corporate Governance Pada Tax Avoidance - Dewi, Gusti Ayu Pradnyanita; Sari, Maria M. Ratna (E-Jurnal Akuntansi, 2015)
Tax avoidance is tax evasion efforts to comply with taxation and use strategies in the field of taxation that are used . This study has purpose to determine the influence of executive incentive, corporate risk, and corporate governance against tax avoidance. The number of samples analyzed 165 samples of companies listed on the Indonesia Stock Exchange (IDX) 2011-2013. Method for this study was purposive sampling. Research data analysis using multiple linear regression. Result of analysis showed a negative effect on the risk of corporate tax avoidance. Executive incentives, institutional ownership, independent directors and audit committee has no effect on tax avoidance. While audit quality has positive influence on tax avoidance.
Keywords: tax avoidance, corporate governance